Pengaruh Manajerial Kepala Madrasah dan Iklim Madrasah terhadap Kompetensi Kepribadian Guru MTs Nurussalam Reak Kecamatan Pujut - Baiq Nurlaela Rahmawati Rahman; Yudin Citriadin; Abdulloh Fuadi (LP2M STIT Palapa Nusantara, 2023)
There are problems in terms of teacher personality competencies that have not been maximized at MTs Nurussalam Reak, Pujut District, Central Lombok. Teachers do not come on time to enter their lessons, there are still teachers who are less sympathetic to students, there are still teachers who are not dressed neatly in class, and there are still teachers who cannot control their emotions when teaching. This causes a lack of response from students, it can be seen that students are depressed when the teacher delivers the subject matter. Based on the problems above, the teacher has not been able to set a good example in terms of discipline and responsibility as a teacher. This can be caused by the managerial head of the madrasa and the unfavorable climate of the madrasa. The type of research used is descriptive method with a quantitative approach. In this study the technique used in data collection was in the form of a closed questionnaire. The intensive research process lasted for almost three months involving 30 teachers at MTs Nurussalam Reak, Pujut District, Central Lombok. Data analysis in this study used multiple regression analysis. the results obtained are: (1) the managerial head of the madrasa has a positive and significant effect on the competence of the teacher's personality, (2) the climate of the madrasa has a positive and significant effect on the competence of the personality of the teacher, (3) the managerial head of the madrasa and the climate of the madrasa together have a significant influence significant to the teacher's personality competence. There is an influence between X1 on Y seen from the value of tcount > ttable, namely 2.397 >t table (2.0484), the managerial head of the madrasah has a positive and significant effect on teacher personality competence. There is an influence between X2 on Y seen from the value of tcount > ttable, namely 3.352 > t table (2.0484), madrasah climate has a positive and significant effect on teacher personality competence. There is an influence between X1 and X2 on Y seen as a significance value > 0.05 and madrasa head managerial and madrasah climate together have a significant influence on teacher personality competence.